Effect of Burning Fire on Fuel Bed Properties in the Dry Deciduous Dipterocarp Forest at Huai Kha Khaeng Wildlife Sanctuary, Uthai Thani Province - Himmapan, Woraphun; Kaitpraneet, San (วารสารวนศาสตร์ไทย, 2022)
Effect of burning fire on fuel bed properties in the dry deciduous dipterocarp forest at Huai Kha Khaeng Wildlife Sanctuary was studied in twelve 30 m x 30 m plots with completely randomized design. Three plots were monthly burned starting from January to April in 2003. Four plots, 1 m x 1 m size of each were selected to study the effect of burning fire on the fuel bed properties. The fuel bed properties were determined before, an immediate after and one, three, six, nine and twelve months after burning. Comparisons of the result differences between pre-burn and post-burn and among the four months burning were made. The results revealed that in pre-burn conditions the average height/depth, moisture content, coverage and load of fuel were 25.57 cm, 50.80 percent, 70.10 percent and 6.86 t ha-1, respectively. Fuel loads ranged from 5.15 t ha-1 to 8.10 t ha-1. The highest total fuel load was found in April. Litter is the main fuel contributing to the forest fire in the dry deciduous dipterocarp forest. Most fuel bed properties were slightly decreased after an immediate burning and showed significantly different after 1 month burning. However, the properties of fuel bed were changed by the weather condition. Fuel moisture contents in this study were relatively high, while fire intensities were low, thus, fuel consumption was relatively low compared to natural forest fires. However, there was a significant loss in load of gross fuel after burning. The mean gross load decreased 49.34 percent after an immediate post-burn. However, the results indicated that one year (twelve months) after a burn, grass was the dominant fuel type as the same as in the pre-burn condition, while height/depth, moisture content and fuel load were roughly 70 percent of the pre-fire state. Keywords: Fire effect, Fuel bed properties, Huai Kha Khaeng, Wildlife Sanctuary